Analysis of trichothecenes in laboratory rat feed by gas chromatography-tandem mass spectrometry. Issue 2 (1st February 2016) - Escrivá, Laura; Manyes, Lara; Font, Guillermina; Berrada, Houda
ABSTRACT: A method for the determination of seven trichothecenes, neosolaniol (NEO), diacetoxyscirpenol (DAS), deoxynivalenol (DON), nivalenol (NIV), fusarenon-X (FUS-X), 3-acetyldeoxynivalenol (3-ADON) and 15-acetyldeoxynivalenol (15-ADON), in laboratory rat feed by GC-MS/MS was developed. Sample extraction and purification was performed by an acidified mixture of acetonitrile/water (80–20% v/v). Limits of quantitation (LOQs) were between 1 and 10 μg kg –1 for all studied trichothecenes. Eight concentration levels between the LOQ and 100 × LOQ were used for the calibration curves. Matrix-matched calibration was used for quantitation purposes to compensate the detector signal enhancement obtained for all the analytes. The method accuracy was evaluated by recovery assays at three concentration levels, 25, 50 and 100 μg kg –1 ( n = 9). Recoveries ranged from 62% to 97% and precision, expressed as intra- and inter-day relative standard deviations, was evaluated for all compounds. The validated method was successfully applied to the analysis of 35 laboratory rat feed samples showing mycotoxin contamination in 66% of the samples. DON was the most prevalent trichothecene followed by 15-ADON, NIV and 3-ADON. The maximum DON concentration reached in real samples was 2156 ± 4.3 μg kg –1, while NEO, DAS and FUS-X were not detected in any sample. Multi-contamination by at least two mycotoxins was observed in 17% of the analysed feed samples.